Litter leaves misrepresent plant–insect interactions in standing vegetation - Adroit, Benjamin; Schachat, Sandra R.; Güner, H. Tuncay; Orts, Jean-Philippe; Denk, Thomas (Frontiers in Ecology and Evolution, 2025)
IntroductionEvidence of insect herbivory on fossilized leaves is widely used to ascertain the evolution of feeding strategies, and trophic changes in response to phenomena such as climate change. However, leaves can decompose somewhat before fossilization, and the extent to which decomposition may bias estimates of insect herbivory in deep time is far from fully understood. There are many points at which evidence may become obscured as a leaf travels from its parent tree into the depositional environment where it fossilizes.Materials & methodsHere, we compare evidence of plant–insect interactions on live leaves and in leaf litter collected directly beneath the same trees to provide an initial glimpse into the first stage at which decomposition may lead to eventual bias in paleontological studies. We measure the frequency and richness of insect damage types on the leaves of Fagaceae in four Mediterranean localities in Turkey and France.Results & discussionWe observed variations in insect damage on litter leaves compared to those on trees, with some localities showing reduced damage richness, lower damage frequency, or both. This observation was particularly pronounced for external damage types. Galls stood out due to their relatively consistent preservation in leaf litter, suggesting their utility as a more dependable indicator for interpreting paleoecological conditions. Our study builds upon existing methods in paleoecology, highlighting their value in detecting environmental signals and advocating for further refinements to capture the ecological dynamics of the past more comprehensively.